Criminal law - Jones, Timothy H.; Taggart, Ian. (2015)
"Now in its 6th edition, this vastly popular text on Scots criminal law has been fully updated and revised to reflect theonward progress of the law since the last edition in 2012. The authors provide not only an essential in-depth explanation of the law but also a highly functional user-friendly tool. Legislative references are fully documented to disclose relevant amendments, valuable websites are referred to and appendices provide guides to bibliographic sources. The text is perfectly designed to be practical and amenable for the busy practitioner or pressured student of Scots criminal law. Criminal Law 6th Edition offers up-to-date coverage of the criminal law of Scotland in a compact and accessible form, relied upon for many years by those with a professional or academic interest in Scots criminal law. The full scope of the text makes Criminal Law 6th Edition the perfect concise modern guide on the subject." --
Nature and sources of Scots criminal law -- Actus reus and mens rea -- Voluntary acts and automatism -- Causation -- Attempt -- Complicity and conspiracy -- Defences Crimes against the person -- Crimes of dishonesty -- Crimes against property -- Crimes relating to public order and morality -- Statutory offences -- Hate crime.
Earlier ed.: 5th, published by W. Breen, 2012.
Includes bibliographical references and index.
Keywords: Criminal law -- Scotland; Criminal law; Scotland